A GERAÇÃO Y E A PUBLICIDADE NA MÍDIA IMPRESSA REVISTA: UMA CONEXÃO POSSÍVEL - Malacrida, Roberto (2011)
The connection established between the advertisements in the print magazine and the youth of so-called Generation Y is the main focus of this work. These young people, born between 1980 and mid-90s, in the twentieth century, developed together with the new communication technologies have grown up with a computer connected to the Internet world with your mobile phone and interactive games, but still being harassed by magazines. In order to better understand this connection, how Gen Y behaves in the face of advertising and see if there is a pattern of use among these young people were conducted exploratory research in primary and secondary sources supplemented by a descriptive study conclusive. After a review of the literature dealing with the concepts of generation to the profile of Generation Y, and a historical analysis of the media magazine, conducting applied research in the form of focus groups and a descriptive study allowed us to conclude that there is a survival for the print magazine, and for a long time. Aspects such as tangibility, portability and tradition are the pillars that ensure solid reliability at a magazine for young people of Generation Y, overlapping with the electronic media, volatile and unreliable for them.